The Relationship Between Retinal Nerve Fiber Layer Thickness and Clinical Symptoms of Alzheimer's Disease - Lian, Teng-hong; Jin, Zhao; Qu, Yuan-zhen; Guo, Peng; Guan, Hui-ying; Zhang, Wei-jiao; Ding, Du-yu; Li, Da-ning; Li, Li-xia; Wang, Xiao-min; Zhang, Wei (Frontiers in Aging Neuroscience, 2021)
Background/Aim: Retinal nerve fiber layer (RNFL) thickness (RT), which can reflect the status of the retinal optic nerve cells, may be affected in patients with Alzheimer's disease (AD). There are few studies on the correlation of RT of patients with AD (AD-RT) with clinical symptoms of various cognitive domains, neuropsychiatric symptoms, and activities of daily living (ADL). This study is to investigate the relationships between RT and the abovementioned clinical symptoms of AD. Methods: A total of 96 patients with AD were included in this study. RT was measured in these patients using optical coherence tomography (OCT). Demographic variables, RT, and clinical symptoms were compared between the normal and the abnormal AD-RT groups. Clinical symptoms, including cognitive symptoms, neuropsychiatric symptoms, and ADL, were evaluated using a series of rating scales. Results: The relationships between RT and cognitive symptoms scores were analyzed in patients with AD. Reduced RT was found in 54.4% of patients with AD. The average RT, RT of the superior 1/2 quadrant, and RT of the inferior 1/2 quadrant of both eyes were all significantly decreased in the abnormal AD-RT group (p < 0.001). Overall cognitive function and performance in multiple cognitive domains, including memory, language, attention, and executive function, were also significantly impaired in the abnormal AD-RT group (p < 0.05). For lower RT value, the global cognitive function and the performance in multiple cognitive domains were worse. ADL was significantly compromised in patients with AD having lower RT values (p < 0.05). Conclusions: Lower RT value appear to be correlated with cognitive impairment, and RT may be an indicator of cognitive decline in patients with AD. Further studies are required to confirm our findings.